Expression Pattern Analyzation and Regulation Genes Identification on the Purple Phenotype in the Different Tissues of the Purple Pak-choi and Zicaitai - Yating Zhu; Xia Wang; Xiuping Tu; Shujiang Zhang; Shifan Zhang; Hui Zhang; Rifei Sun; Xiuxiu Xu; Xinyu Gao; Guoliang Li; Fei Li (Horticulturae, 2025)
Among the Brassica species in China, including Chinese cabbage, pak-choi, caixin, zicaitai, and wucai, Brassica rapa plays an important role in vegetable production. Purple resources from the species itself are scarce. It is worth noting that the tissue positions expressing a purple phenotype vary greatly between purple pak-choi and zicaitai. In this study, the genetic patterns of the purple phenotype were analyzed in purple pak-choi and zicaitai, and the F1 showed purple leaves and green stems, which indicated that purple traits in the leaves and stem were inherited independently. In conjunction with field identification, RNA-seq was used to sequence the transcriptomes of the purple expression sites of purple pak-choi, zicaitai, and their F1. The high expression of the regulatory genes Dark_pur and BrTT8 affected the purple color of pak-choi and caused the high expression of structural genes of the anthocyanin metabolism pathway and the accumulation of anthocyanins in leaves. The regulatory genes BrPAP2 and BrTT8 affected the purple color of zicaitai stems, were significantly upregulated, and caused high expression of related structural genes, leading to the accumulation of anthocyanins in the stem epidermis. This suggested that BrPAP2 and Dark_pur were both R2R3-MYB transcription factors, which were tissue-specific for the regulation of purple color traits in B. rapa. They also had a gene epistatic effect, which influenced the expression of purple traits in the F1. The gene MYBL2 was highly expressed in all purple tissue sites. The present study on the regulatory genes of the purple phenotype of zicaitai and purple pak-choi provides a theoretical basis for revealing the influence of purple traits on B. rapa leaves and stems, and it may lay the foundation for the selection and breeding of purple vegetables of B. rapa.